New Labour and the New World Order : Britain's Role in the War on Terror. - Kettell, Steven (Manchester University Press, 2011)
The war on terror has shaped and defined the first decade of the 21st century, yet analyses of Britain's involvement remain limited and fragmentary. This book provides a comprehensive analysis of these developments. It argues that New Labour's support for a militaristic campaign was driven by a desire to elevate Britain's influence on the world stage, and to assist the United States in a new imperialist project of global reordering. Ostensibly set within a political framework of promoting humanitarian values, the government's conduct in the war on terror also proved to be largely counter-productive, eroding trust between the citizenry and the state, putting the armed forces under increasing strain and ultimately exacerbating the threat from radical Islamic terrorism. This book will be of interest to teachers and scholars of British foreign policy, international relations and security studies. It will also appeal to anyone interested in Britain's role in the war on terror.